2023
DOI: 10.1177/00111287221143931
|View full text |Cite
|
Sign up to set email alerts
|

Brief Measure of Affective Lability Among Portuguese Community and Justice Samples: Psychometrics and Measurement Invariance

Abstract: Affective lability is a central feature of several emotional disturbances and is linked to aggressive and risky behaviors. This study aimed to analyze the psychometric properties of the Affective Lability Scale-18 (ALS-18) among a community sample and a sample of justice-involved adults. We also aimed to test the measurement invariance between sex and sample type. Results revealed good to excellent values of internal consistency. Confirmatory factor analysis indicated that the original three-factor structure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…In the present study, relevant results for Psychology are found since we identified a relationship between the studied variables, allowing us to expand the knowledge about human behavior and the factors that can influence it at the emotional and behavioral levels. Some recent studies identify the negative impact of childhood experiences across lifelong (e.g., Almeida et al, 2023a , b ; Pires & Almeida, 2023 ), and other ones identify some protective factors to develop a healthy life in adulthood (e.g., Almeida et al, 2023b ; Letourneau et al, 2020 ). Discovering potential risk and protective factors is essential to create intervention programs that can be implemented, for example, in the National Justice System, with victims and offenders.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, relevant results for Psychology are found since we identified a relationship between the studied variables, allowing us to expand the knowledge about human behavior and the factors that can influence it at the emotional and behavioral levels. Some recent studies identify the negative impact of childhood experiences across lifelong (e.g., Almeida et al, 2023a , b ; Pires & Almeida, 2023 ), and other ones identify some protective factors to develop a healthy life in adulthood (e.g., Almeida et al, 2023b ; Letourneau et al, 2020 ). Discovering potential risk and protective factors is essential to create intervention programs that can be implemented, for example, in the National Justice System, with victims and offenders.…”
Section: Discussionmentioning
confidence: 99%